Analisis Peran Wanita Generasi Milenial pada Usaha Mikro Kecil Menengah di dalam Era Ekonomi Digital di Kepulauan Riau Indonesia - Afrianti Elsye Vanomy; Ibnu Harris (University of Merdeka Malang, 2021)
This research can provide the illustration and answers about what millennial generation women must prepare who run MSME’s. The research method is a quantitative approach, collecting data with questionaries and using purposive sampling, the study uses partial least square structural equation modelling analysis test. The amount of data used is 110 respondents. The object of research is the women entrepreneurs in Riau Islands who are in the age range of 21 to 41 years. The results of the study of discrimination factors, motivation, demographics had a significant positive effect on Capabilities, Commitment Factors, Financial Access Factors had a positive insignificant effect on Capabilities. Capability has a significant positive effect on MSME’s Human Capital, MSME’s Human Capital has a significant positive effect on the Digital Economy.